The professional researcher as change agent in the government-performance movement - Coplin, William D.; Bourdeaux, Carolyn; Merget, Astrid E. (2002)
Although academic and professional publications give the impression that performance measurement is a growing government practice, in actuality the use of this technology is not as deep or as widespread as it may appear. Even when performance measures are used, governments rarely integrate them into planning, budget, personnel, and other management processes. Most professional researchers located primarily in academic institutions, but also in research and government organizations, approach, performance measurement as though governmental officials, elected or otherwise, are already sold on its usefulness. Instead, they need to function as "change agents", using a variety of strategies to gain acceptance and u nderstanding of the strengths and limitations of performance measurement. This article draws on the authors' experiences with the Community Benchmarks Program of the Maxwell School in Onondaga County and a review of the current literature. It suggests guidelines for professional researchers who want to increase the use of performance measures by governments at all levels. - Reproduced.
Keywords: Performance appraisal